1986
DOI: 10.1029/gl013i008p00737
|View full text |Cite
|
Sign up to set email alerts
|

A new mechanism for stable viscous remanent magnetization and overprinting during long magnetic polarity intervals

Abstract: A neW.. mechanism by which viscous remanent magnetization, VRM, can be acquired is Proposed. This VRM probably is the major cause of overprinting during long magnetic polarity intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Studies of secondary fluid inclusions and burial histories from apatite and zircon fission‐track cooling ages should be helpful. Additional studies of TVRM acquisition during long polarity intervals [e.g., Moon and Merrill, 1986] might also be productive.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of secondary fluid inclusions and burial histories from apatite and zircon fission‐track cooling ages should be helpful. Additional studies of TVRM acquisition during long polarity intervals [e.g., Moon and Merrill, 1986] might also be productive.…”
Section: Discussionmentioning
confidence: 99%
“…During the last few years there has, unfortunately, been little improvement in the available data from the stable cratonic areas of the major Gondwanan continents, with the notable exception of Australia, for which there has been both re-sampling and re-analysis (Embleton 1981;Idnurm 1985aIdnurm ,b 1986. In fact, most advances have resulted in an increasing appreciation of the complexities of the magnetic processes, even when only time is involved (Moon and Merrill 1986). This has resulted in the elimination, or at least questioning, of the reliability of most previously accepted observations.…”
Section: Continental Palaeomagnetismmentioning
confidence: 99%
“…As all other evidence indicates that the sequence is older than the Brunhes, we must conclude that the overprint signal has a high coercivity. Moon and Merrill (1986) showed that high coercivity VRM can occur, and there always remains the possibility that the high coercivity overprint is partly of post-depositional chemical origin. Below the estimated position of the B/M boundary, the records at both Sites 821 and 820 are too poor to merit any sort of polarity interpretation.…”
Section: Polarity At Sites 821 and 820mentioning
confidence: 99%